2017
DOI: 10.1002/anie.201702882
|View full text |Cite
|
Sign up to set email alerts
|

SN2 Reactions at Tertiary Carbon Centers in Epoxides

Abstract: Described herein is a novel concept for S 2 reactions at tertiary carbon centers in epoxides without activation of the leaving group. Quantum chemical calculations show why S 2 reactions at tertiary carbon centers are proceeding in these systems. The reaction allows flexible synthesis of 1,3-diol building blocks for natural product synthesis with excellent control of the relative and absolute configurations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Due to the lack of one electron compared with carbon, unlike graphene, the 2D honeycomb boron structure is typically unstable. As pointed out by Zhang et al 47 and Shirodkar et al 48 , a possible approach to stabilize honeycomb boron is by electron doping. The recent experimental breakthrough by Li et al 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the lack of one electron compared with carbon, unlike graphene, the 2D honeycomb boron structure is typically unstable. As pointed out by Zhang et al 47 and Shirodkar et al 48 , a possible approach to stabilize honeycomb boron is by electron doping. The recent experimental breakthrough by Li et al 36 .…”
Section: Resultsmentioning
confidence: 99%
“…As an extension of work on fluoride catalysis, Gansäuer et al reported the fluoride-catalyzed stereospecific hydrosilylationo f ar ange of a-hydroxy epoxides (Scheme 14). [26] The reaction with PhSiH 3 (4 equiv) proceeded at 25 8Ct hrough an intramolecular S N 2h ydride transfer in the presence of 20-50 mol % TBAF.E poxide opening took place exclusively at the tertiary carbonc enter to provide the corresponding 1,3-diols in good to excellent yields, with > 99:1 d.r.I nc ontrast, conventional catalytic reduction systemso fB F 3 /NaBH 3 CN [27] and Red-Al [28] showedahigh preference towards 1,2-diolformation.…”
Section: Hydrosilylative Reduction Of Epoxidesmentioning
confidence: 99%
“…As an extension of work on fluoride catalysis, Gansäuer et al. reported the fluoride‐catalyzed stereospecific hydrosilylation of a range of α‐hydroxy epoxides (Scheme ) . The reaction with PhSiH 3 (4 equiv) proceeded at 25 °C through an intramolecular S N 2 hydride transfer in the presence of 20–50 mol % TBAF.…”
Section: Hydrosilylative Reduction Of Epoxidesmentioning
confidence: 99%
“…Such methods usually suffer from poor regioselectivities by providing a mixture of both primary and secondary alcohols, poor functional group tolerance, and the generation of enormous amounts of waste. Heterogeneous ( Duval et al., 2021 ; Thiery et al., 2007 ; Nandi et al., 2017 ) and particularly homogeneous transition-metal catalyzed hydrogenation ( Yao et al., 2019 ; Liu et al., 2019 ), hydroboration ( Patnaik and Sadow, 2019 ; Song et al., 2017 ; Desnoyer et al., 2017 ), and hydrosilylation ( Zhang et al., 2017 , 2018 ; Wenz et al., 2017 ; Henriques et al., 2016 ; Gansäuer et al., 2012 ; Park and Brookhart, 2011 ; Nagashima et al., 2000 ) of epoxides as well as transition-metal-free approaches ( Patnaik and Sadow, 2019 ; Zhang et al., 2018 ; Huang et al., 2022 ; Ton et al., 2021 ) were developed by several laboratories leading preferentially to anti -Markovnikov alcohols. Many fewer catalysts have been reported for the selective reduction of epoxides into Markovnikov alcohols.…”
Section: Introductionmentioning
confidence: 99%